Działalność naukowa Jana Kuchty - Wnęk, Jan (Biuletyn Historii Wychowania, 2011)
The article presents the scholarly activity of Jan Kuchta in the interwar period and discusses the contents of his articles and books. The author discusses in detail the essential contents of the following books: Książka zakazana jako przedmiot zainteresowań młodzieży w okresie dojrzewania („A Forbidden Book As an Object of Interest of Adolescent Youth”); Dziecko włóczęga (“A Child Vagabond”); Nowe kierunki i dążenia współczesnej katolickiej pedagogiki [na tle obrazu chaosu we współczesnym wychowaniu] (“New Trends and Endeavours of Catholic Pedagogics [on the Background of the Image of Chaos in Modern Upbringing])”. These books, as well as other Kuchta’s works, popularized a number of problems from various fields of knowledge, such as ethnography, pedagogy, psychology and sociology. However, these were not creative treaties constituting a significant contribution to the Polish science.